Metode Multimedia Development Life Cycle Pada Media Pembelajaran Pengenalan Perangkat Komputer Bagi Siswa Sekolah Dasar - Dyan Yuni Pramesti; Rita Wahyuni Arifin (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2020)
The condition of the students who sit in elementary school but difficulty in attending computer recognition lessons, the teacher in explaining the material is not accompanied by props so that elementary school students have difficulty in following computer recognition lessons. Based on existing problems the author tries to design a learning media prop in explaining the lessons of computer device introduction. This learning medium contains written materials, videos, Multiple Choice Quiz, and Puzzles. The method used is Multimedia Development Life Cycle (MDLC) where this method is arranged based on 6 (six) stages namely concept, design, obtaining content material, assembly, testing, and distribution. In this study the authors were only new to the assembly stage. With this learning media, it is expected that elementary school children can know the form of computer devices and understand how to use them, as well as learning activities become more interesting, effective and able to foster students' learning interest in knowing computers. Keywords: Learning Media, Elementary School, MDLC, Computer, Introduction Abstrak Kondisi siswa yang duduk di bangku sekolah dasar kelas namun kesulitan dalam mengikuti pelajaran pengenalan komputer, guru dalam menjelaskan materi tidak disertai dengan alat peraga sehingga siswa sekolah dasar kesulitan dalam mengikuti pelajaran pengenalan komputer. Berdasarkan masalah yang ada penulis mencoba merancang sebuah media belajar alat peraga dalam menjelaskan pelajaran pengenalan perangkat komputer. Media pembelajaran ini berisi mengenai materi tertulis, video, Quiz Pilihan Ganda, dan Puzzle. Metode yang digunakan adalah Multimedia Development Life Cycle (MDLC) dimana metode ini tersusun berdasarkan 6 (enam) tahapan yaitu concept, design, obtaining content material, assembly, testing, dan distribution. Dalam penelitian ini penulis hanya baru sampai tahap assembly. Dengan adanya media pembelajaran ini diharapkan anak sekolah dasar dapat mengetahui bentuk perangkat komputer dan mengerti cara penggunaannya, serta kegiatan belajar menjadi lebih menarik, efektif serta mampu menumbuhkan minat belajar siswa dalam mengenal komputer. Kata kunci: Media Pembelajaran, Sekolah Dasar, MDLC, Komputer, Pengenalan